2012
DOI: 10.3390/cancers4030701
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Stroma: Pathophysiology and the Roles in Cancer Development

Abstract: Ovarian cancer represents one of the cancers with the worst prognostic in adult women. More than half of the patients who present with clinical signs such as abdominal bloating and a feeling of fullness already show advanced stages. The majority of ovarian cancers grow as cystic masses, and cancer cells easily spread into the pelvic cavity once the cysts rupture or leak. When the ovarian cancer cells disseminate into the peritoneal cavity, metastatic nests may grow in the cul-de-sac, and in more advanced stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 128 publications
(148 reference statements)
2
21
0
Order By: Relevance
“…Breast and ovarian cancer genes such as BRCA1 and BRCA2 are identified through analyzing germ line mutations in familial cases (13,14), and their somatic mutations are largely undetectable in advanced tumors (15), which is evidence against the possibility for clonal expansion of a mutant progenitor into tumor parenchyma. In contrast, mounting evidence supports a link of cancer initiation to altered tumor microenvironment in tumor stroma (16,17); stroma is the particular natural habitat of progenitor cells. In ovarian cancer, steroid hormone-producing cells have been observed in tumor stroma promoting inclusion cysts and epithelial tumor cells (18).…”
mentioning
confidence: 97%
“…Breast and ovarian cancer genes such as BRCA1 and BRCA2 are identified through analyzing germ line mutations in familial cases (13,14), and their somatic mutations are largely undetectable in advanced tumors (15), which is evidence against the possibility for clonal expansion of a mutant progenitor into tumor parenchyma. In contrast, mounting evidence supports a link of cancer initiation to altered tumor microenvironment in tumor stroma (16,17); stroma is the particular natural habitat of progenitor cells. In ovarian cancer, steroid hormone-producing cells have been observed in tumor stroma promoting inclusion cysts and epithelial tumor cells (18).…”
mentioning
confidence: 97%
“…Hence, the cells are immunoreactive for some of the epithelial and mesothelial cell markers. (14) The few studies done in recent past on mesothelin expression in ovarian tumours and present study suggest that ovarian epithelial tumours show variable mesothelin expression. The present study revealed mesothelin positivity (100%) in all benign and malignant serous tumours.…”
Section: Discussionmentioning
confidence: 88%
“…The inflammatory response is one of the signature features of tumor development and plays an important role in tumor progression . Research on the diagnosis and prognosis of various inflammatory cells has become a targeted area of interest in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays an important role in the occurrence and development of cancer . Therefore, cancer is also widely considered a cause chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%